Constructing a Maqāṣid-Ecological Interpretation Paradigm: Integrating Islamic Ecotheology and Qur’anic Environmental Ethics in Indonesia - Moh. Fatkhur Rohman; Abd. Kholid (AL QUDS : Jurnal Studi Alquran dan Hadis, 2026)
Environmental degradation in Indonesia, including deforestation, marine pollution, flooding, and climate-related crises, has become an urgent challenge requiring not only technical solutions but also ethical and religious responses. Although environmental issues have received increasing attention in contemporary Qur’anic studies, existing scholarship generally discusses ecological ethics and Islamic ecotheology separately from the maqāṣid al-sharī‘ah framework. Consequently, a comprehensive interpretive model integrating Qur’anic environmental teachings, Islamic ecotheology, and the higher objectives of Islamic law remains underdeveloped. This study aims to formulate a Maqāṣid-Ecological Interpretation Paradigm to address environmental issues and strengthen Qur’anic environmental ethics in Indonesia. Employing a qualitative library research method, the study analyzes Qur’anic verses concerning khalīfah (Q. al-Baqarah [2]:30), fasād (Q. al-Rūm [30]:41), and mīzān (Q. al-Raḥmān [55]:7–9) through a descriptive-analytical approach. Primary data consist of relevant Qur’anic verses, while secondary data are derived from classical and contemporary tafsīr works, studies on maqāṣid al-sharī‘ah, Islamic ecotheology, and environmental ethics. The findings reveal that environmental preservation constitutes an integral part of the objectives of Islamic law, particularly the protection of life (ḥifẓ al-nafs), wealth (ḥifẓ al-māl), and future generations (ḥifẓ al-nasl). The integration of khalīfah, mīzān, and fasād provides an ethical framework for addressing deforestation, marine pollution, and the energy crisis. This study proposes the Maqāṣid-Ecological Interpretation Paradigm, which reorients Qur’anic interpretation toward transformative ecological engagement and contributes to the development of sustainable Qur’anic environmental ethics in Indonesia.